ANALISIS PENGARUH FAKTOR-FAKTOR FUNDAMENTAL PERUSAHAAN TERHADAP MASUK ATAU KELUARNYA PERUSAHAAN DARI INDEKS LQ45 (Studi Kasus Perusahaan yang terdapat pada Indeks LQ45 2009-2013) - Hisyam Luthfi; P. Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2014)
The company list change included in LQ45 index calculation was done to make LQ45 index adjustment to market condition. The factor of fundamental firm that can affect added or deleted firm from LQ45 index will affect investment behavior of the investor. This research was done to analyze the impact of fundamental firm factors to market beta at LQ45 index in the period of 2009-2013. This research is replication of a research done by Geppert, et al (2011) and in this research using the LQ45 index as the object under study. Delta beta firm, delta correlations, delta stock variation, and delta market variation were used in the research done by Geppert, et al (2011) to analyze fundamental firm to market beta.            The population of this research was the companies that listed in LQ45 index in the period of 2009-2013. The total samples were 108 companies that added or deleted from LQ45 index in the period of 2009-2013. Ordinary Least Square (OLS) was used in this research as a regression analysis.            The result of this research showed that the delta beta firm, delta correlations, delta stock variation, and delta market variation did not have any significant effect to market beta. The impication of this research showed that added or deleted companies from LQ45 index were not influenced by changes in the firm’s fundamental, but rather to the market capitalization, trading activity, financial condition and growth prospects of the company.